Preparation method of cigarette core material with high thermal conductivity as well as product and application of cigarette core material

By hydroxylation modification of the thermal filler and grafting the silane coupling agent, combined with the hot pressing process, the thermal filler is evenly distributed on the smoke core material, solving the problem of insufficient thermal conductivity of the heating cigarette, and significantly improving the thermal conductivity coefficient and thermal conductivity uniformity.

CN119823452APending Publication Date: 2025-04-15CHINA TOBACCO JIANGSU INDAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510098540.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The thermal conductivity of existing heated cigarettes is insufficient, resulting in uneven heat conduction, affecting the atomization and volatility of tobacco substances, and reducing the utilization rate of tobacco materials.

Method used

By surface hydroxylation modification of the thermal filler and grafting of the silane coupling agent, modified thermal filler nanoparticles are formed, and uniformly coated on the smoke core material by impregnation or spraying. Combined with the hot pressing process, the thermal filler is evenly distributed to form a thermal path.

Benefits of technology

It significantly improves the thermal conductivity coefficient of the cigarette core material, solves the problem of large amount of thermal conductivity filler addition, and improves the thermal conductivity uniformity of the heated cigarette and the atomization efficiency of tobacco substances.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of a high-thermal-conductivity cigarette core material and a product and application of the high-thermal-conductivity cigarette core material, and the preparation method comprises the following steps: dispersing thermal conductive filler powder in a stripping solvent for stripping and hydroxylation treatment to obtain hydroxylated thermal conductive filler nanoparticles; dispersing the hydroxylated heat-conducting filler nanoparticles in a solution containing a silane coupling agent, and carrying out heating treatment to obtain silane coupling agent modified heat-conducting filler nanoparticles; mixing the silane coupling agent modified heat-conducting filler nanoparticles with an adhesive aqueous solution, and carrying out dispersion treatment to obtain heat-conducting slurry; the heat conduction slurry is distributed on the surface of the cigarette core material, drying treatment is carried out, then hot pressing treatment is carried out, and the high-heat-conductivity cigarette core material is obtained. The method not only solves the problem of large addition amount of the heat-conducting filler, but also greatly improves the heat conductivity coefficient of the cigarette core material; the preparation method is simple and easy to operate, green, low in production cost, simple in process and high in benefit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cigarette core materials, and relates to a preparation method of a high thermal conductivity cigarette core material and a product and application thereof. Background Art

[0002] Heated cigarettes are one of the important categories of new tobacco products. They generally deliver satisfaction and some tobacco flavor to consumers by heating but not burning tobacco. Their appearance and consumption methods are no different from traditional cigarettes. This "heating without burning" method heats tobacco only at a relatively low temperature (ideal temperature range 250-350℃), and avoids the production of tar and a large number of harmful compounds during combustion through high-temperature pyrolysis.

[0003] However, due to the low thermal conductivity of tobacco itself and the limitations of the area of ​​heating components, the heat conduction is not uniform whether it is peripheral heating or inner core heating, and the analysis of volatile components in different areas is inconsistent. The temperature of tobacco material close to the heat source is higher, and the atomization medium, aroma components and added flavors and fragrances contained in the tobacco material can be better atomized and volatilized, while the tobacco material far away from the heat source is the opposite, which reduces the utilization rate of tobacco material. If the tobacco material far away from the heat source is to reach the atomization temperature, the required heating temperature is too high, which will cause the tobacco near the heat source to coke, which is not conducive to the sensory quality of the cigarette. Therefore, it is very important to improve the thermal conductivity of the heated cigarette core material.

[0004] Current research has found that optimizing the preparation process of tobacco core materials and adding thermal conductive additives are effective ways to improve the thermal conductivity of heated cigarettes. It is feasible to improve the heat transfer capacity by evenly covering the surface of tobacco with thermal conductive fillers through spraying, dipping, coating or printing to form a thermal conductive path. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for preparing a high thermal conductivity cigarette core material and its product and application.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a high thermal conductivity cigarette core material, the preparation method comprising the following steps:

[0008] (1) dispersing a thermally conductive filler powder in a stripping solvent for stripping and hydroxylation to obtain hydroxylated thermally conductive filler nanoparticles;

[0009] (2) dispersing the hydroxylated thermally conductive filler nanoparticles in a solution containing a silane coupling agent and performing a heat treatment to obtain thermally conductive filler nanoparticles modified with a silane coupling agent;

[0010] (3) mixing the thermally conductive filler nanoparticles modified by the silane coupling agent with the adhesive aqueous solution for dispersion treatment to obtain a thermally conductive slurry;

[0011] (4) Distributing the thermal conductive slurry on the surface of the cigarette core material, drying it, and then heat-pressing it to obtain the high thermal conductive cigarette core material.

[0012] The present invention develops a new method for preparing a high thermal conductivity cigarette core material, which is to modify the surface of a thermally conductive filler by hydroxylation, then graft a silane coupling agent onto the surface of the thermally conductive filler, and then uniformly coat the modified thermally conductive filler on the cigarette core material by an impregnation method or a spraying method, and then use a hot pressing process to evenly distribute the thermally conductive filler on the surface of the cigarette core material to form a thermal conductive path. This method not only solves the problem of a large amount of thermally conductive filler added, but also greatly improves the thermal conductivity of the cigarette core material; the preparation method is easy to operate, green, low in production cost, simple in process, and high in efficiency.

[0013] Preferably, the thermally conductive filler in step (1) is selected from any one of boron nitride, aluminum nitride, graphene oxide, carbon nanotubes, silicon carbide, magnesium oxide, aluminum oxide, zinc oxide, silicon dioxide or thermally conductive metal powder, or a combination of at least two thereof.

[0014] The preparation method of the high thermal conductivity cigarette core material involved in the present invention can use the above-mentioned thermal conductive filler commonly used in the art as a modified base material, perform hydroxylation modification and silane coupling agent modification on it, and then coat it on the cigarette core material to obtain the high thermal conductivity cigarette core material.

[0015] Preferably, the mass ratio of the thermally conductive filler powder to the stripping solvent in step (1) is (0.1-5):100, for example, 0.1:100, 0.5:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100, 5:100, etc.

[0016] Preferably, the stripping solvent in step (1) is a mixed solution of water and any one or at least two of the following organic solvents: isopropanol, isobutanol, ethanol, polyvinyl alcohol, DMF (N,N-dimethylformamide).

[0017] Preferably, the volume ratio of water to organic solvent is 1:(0.8-1.2), for example, 1:0.8, 1:0.9, 1:0.95, 1:1, 1:1.1, 1:1.2, etc.

[0018] The stripping solvent used in the preparation method of the present invention is preferably a mixed solution of water and any one or at least two of the organic solvents listed above. Compared with pure water or pure organic solvent, it has better stripping and hydroxylation effects on thermal conductive fillers, and the thermal conductivity of the final product is higher.

[0019] Preferably, the stripping solvent is a mixed solution of water, isopropanol and ethanol.

[0020] Among the many options for stripping solvents, the present invention has creatively discovered that when a mixed solution of water, isopropanol and ethanol is used as the stripping solvent, the stripping and hydroxylation effects on the thermally conductive filler are better, and the thermal conductivity of the final product is higher.

[0021] Preferably, the volume ratio of isopropanol to ethanol is (3-5):1, for example 3:1, 3.5:1, 3.8:1, 4:1, 4.2:1, 4.4:1, 4.5:1, 4.8:1, 5:1, etc.

[0022] Preferably, the stripping and hydroxylation treatment in step (1) is carried out under ultrasound, and the ultrasound temperature is 15-40°C, for example, 15°C, 18°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc.; the ultrasound time is 10-24h, for example, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, etc.

[0023] Preferably, the solution in step (2) is a mixed solution of water and any one or at least two of the following organic solvents: isopropanol, isobutanol, ethanol, polyvinyl alcohol, DMF (N,N-dimethylformamide).

[0024] Preferably, the volume ratio of water to organic solvent is 1:(2-4), for example 1:2, 1:2.2, 1:2.4, 1:2.5, 1:2.7, 1:3, 1:3.2, 1:3.5, 1:3.8, 1:4, etc.

[0025] The reaction medium for silane coupling treatment in the preparation method of the present invention is preferably a mixed solution of water and any one or at least two of the organic solvents listed above. Compared with pure water or pure organic solvent, the silane coupling agent has a better modification effect on the thermally conductive filler, and the thermal conductivity of the final product is higher.

[0026] Preferably, the solution is a mixed solution of water and ethanol.

[0027] Compared with other types of organic solvents, the mixed solution of ethanol and water selected here can make the silane coupling agent have a better modification effect on the thermal conductive filler, and the thermal conductivity of the final product is higher.

[0028] Preferably, in the solution containing the silane coupling agent in step (2), the mass percentage of the silane coupling agent is 0.1-1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.

[0029] Preferably, the silane coupling agent in step (2) is selected from any one of KH550, KH560, KH570, A151, A171 or Si-69, or a combination of at least two thereof.

[0030] Preferably, the silane coupling agent in step (2) is selected from KH550 and / or KH570.

[0031] Compared with other types of silane coupling agents, the selection of KH550 and / or KH570 here can make the modification effect of the silane coupling agent on the thermal conductive filler better, and the thermal conductivity of the final product is higher. The combination of KH550 and KH570 is more preferred.

[0032] Preferably, the mass ratio of the hydroxylated thermally conductive filler nanoparticles to the solution containing the silane coupling agent in step (2) is (0.1-5):100, for example, 0.1:100, 0.5:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100, 5:100, etc.

[0033] Preferably, the heating treatment in step (2) is carried out in a flowing oil bath at 90-100°C (e.g., 90°C, 92°C, 94°C, 96°C, 98°C, 100°C, etc.) with stirring and condensing for 18-30h (e.g., 18h, 20h, 22h, 24h, 26h, 28h, 30h, etc.).

[0034] Preferably, the binder in step (3) is selected from any one of sodium alginate, sodium carboxymethyl cellulose, chitosan, guar gum or cellulose acetate, or a combination of at least two thereof.

[0035] Preferably, in step (3), the mass ratio of the thermally conductive filler nanoparticles modified by the silane coupling agent to the adhesive is (1-5):1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, etc.

[0036] Preferably, the concentration of the aqueous binder solution in step (3) is 0.25-1%, for example 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.

[0037] Preferably, the dispersion treatment in step (3) is carried out under ultrasound, and the ultrasound temperature is 15-40°C, for example, 15°C, 18°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc.; the ultrasound time is 8-24h, for example, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, etc.

[0038] Preferably, the cigarette core material in step (4) is in the shape of a thin sheet.

[0039] Preferably, the distribution method in step (4) includes dipping or spraying.

[0040] The dipping method is to immerse the cigarette core material in the thermal conductive slurry for 2-30 seconds and then take it out, for example, 2s, 10s, 15s, 18s, 20s, 25s, 30s, etc.; the spraying method is to evenly spray the thermal conductive slurry on the surface of the cigarette core material.

[0041] Preferably, the drying treatment in step (4) is carried out at 40-60°C (e.g., 40°C, 45°C, 40°C, 45°C, 60°C, etc.) and a humidity of 50-70% (e.g., 50%, 55%, 60%, 65%, 70%, etc.) RH.

[0042] Preferably, the dry weight of the thermal conductive slurry in step (4) is loaded on the surface of the cigarette core material in an amount of 0.1-1 mg / cm 2 , for example 0.1 mg / cm 2 , 0.2mg / cm 2 , 0.3mg / cm 2 , 0.4mg / cm 2 , 0.5mg / cm 2 , 0.6mg / cm 2 , 0.7mg / cm 2 , 0.8mg / cm 2 , 1mg / cm 2 wait.

[0043] Preferably, the hot pressing treatment in step (4) is carried out at 30-50°C (e.g., 30°C, 35°C, 40°C, 45°C, 50°C, etc.) and a pressure of 5-14MPa (e.g., 5MPa, 7MPa, 8MPa, 10MPa, 12MPa, 13MPa, 14MPa, etc.).

[0044] In a second aspect, the present invention provides a high thermal conductivity cigarette core material prepared according to the preparation method described in the first aspect.

[0045] In a third aspect, the present invention provides use of the high thermal conductivity cigarette core material according to the second aspect in preparing heated cigarettes.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] The present invention develops a new method for preparing a high thermal conductivity cigarette core material, which is to modify the surface of a thermally conductive filler by hydroxylation, then graft a silane coupling agent onto the surface of the thermally conductive filler, and then uniformly coat the modified thermally conductive filler on the cigarette core material by an impregnation method or a spraying method, and then use a hot pressing process to evenly distribute the thermally conductive filler on the surface of the cigarette core material to form a thermal conductive path. This method not only solves the problem of a large amount of thermally conductive filler added, but also greatly improves the thermal conductivity of the cigarette core material; the preparation method is easy to operate, green, low in production cost, simple in process, and high in efficiency. DETAILED DESCRIPTION

[0048] In order to further explain the technical means and effects adopted by the present invention, the technical solution of the present invention is further described below in conjunction with the preferred embodiments of the present invention, but the present invention is not limited to the scope of the embodiments.

[0049] The thermal conductivity of the tobacco sheets before modification used in the following examples and comparative examples was measured by a thermal conductivity tester (TC 3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) to be 0.10 W·m -1 ·K -1 .

[0050] Example 1

[0051] This embodiment provides a method for preparing a high thermal conductivity cigarette core material, which is specifically as follows:

[0052] (1) 1.5 g of h-BN powder was dispersed in 300 mL of a mixed solution of isopropanol and deionized water (volume ratio 1:1), and the mixed solution was ultrasonically exfoliated at 30 °C for 12 h;

[0053] (2) centrifuging the mixed solution after stripping at 2000 rpm for 10 min, vacuum filtering the supernatant obtained after centrifugation, and drying to obtain hydroxylated h-BN nanoparticles (OH-hBN);

[0054] (3) 0.2 g of OH-hBN was added to a mixed solution of 200 mL of ethanol and deionized water (volume ratio 3:1), and ultrasonically dispersed at 30°C for 1 h. Then, 0.5 mL of silane coupling agent KH550 was added to the mixed solution, and stirred in an oil bath at 100°C for 24 h under condensation reflux;

[0055] (4) After the solution is cooled to 25° C., the mixed solution is filtered, and the filtrate is dried at 100° C. for 12 h to obtain h-BN nanoparticles modified with a silane coupling agent;

[0056] (5) Weigh 0.5 g of sodium alginate and dissolve it in 99.5 g of deionized water to prepare a 0.5% sodium alginate aqueous solution, then add 1 g of the h-BN nanoparticles modified by the silane coupling agent, and stir ultrasonically at 30° C. for 6 h to obtain a thermal conductive slurry;

[0057] (6) Dipping the tobacco slices into the thermal conductive slurry, vertically dipping and taking them out, the dipping time is 5 seconds;

[0058] (7) Dry the impregnated tobacco sheet at 50°C and 60% RH for 3 hours; the dry weight of the thermal conductive slurry on the surface of the tobacco sheet is 0.4 mg / cm 2 ;

[0059] (8) The tobacco slices were hot-pressed for 0.5 h using a flat plate vulcanizer at a pressure of 10 MPa and a temperature of 30° C. to obtain a high thermal conductivity tobacco core material.

[0060] The thermal conductivity of the cigarette core material obtained in this embodiment was measured by a thermal conductivity tester (TC 3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) and found to be 0.26 W·m -1 ·K -1 .

[0061] Example 2

[0062] This embodiment provides a method for preparing a high thermal conductivity cigarette core material, which is specifically as follows:

[0063] (1) 3 g of nano-aluminum nitride powder (30-50 nm) was dispersed in 300 mL of a mixed solution of isopropanol and deionized water (volume ratio 1.2:1), and the mixed solution was ultrasonically exfoliated at 35 °C for 16 h;

[0064] (2) centrifuging the mixed solution after stripping at 2000 rpm for 10 min, vacuum filtering the supernatant obtained after centrifugation, and drying to obtain hydroxylated nano-aluminum nitride particles;

[0065] (3) 1 g of hydroxylated nano-aluminum nitride particles was added to a mixed solution of 200 mL of ethanol and deionized water (volume ratio 2:1), and ultrasonically dispersed at 35°C for 1 h. Then, 1 mL of silane coupling agent KH560 was added to the mixed solution, and stirred in an oil bath at 100°C for 30 h under condensation reflux;

[0066] (4) After the solution is cooled to 25° C., the mixed solution is filtered, and the filtrate is dried at 100° C. for 12 h to obtain nano-aluminum nitride particles modified with a silane coupling agent;

[0067] (5) Weigh 1 g of sodium carboxymethyl cellulose and dissolve it in 99 g of deionized water to prepare a 1% sodium carboxymethyl cellulose aqueous solution, then add 1 g of the nano-aluminum nitride particles modified by the silane coupling agent, and stir ultrasonically at 35° C. for 12 h to obtain a thermal conductive slurry;

[0068] (6) using a pneumatic spray gun to evenly spray the thermal conductive slurry onto the surface of the tobacco sheet;

[0069] (7) Drying the impregnated tobacco sheet at 40° C. and 50% RH, the dry weight loading of the thermal conductive slurry being the same as that in Example 1, and the drying time being 4 h;

[0070] (8) The tobacco slices were hot-pressed for 0.5 h using a flat plate vulcanizer at a pressure of 14 MPa and a temperature of 40° C. to obtain a high thermal conductivity tobacco core material.

[0071] The thermal conductivity of the cigarette core material obtained in this embodiment was measured by a thermal conductivity tester (TC 3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) and found to be 0.25 W·m -1 ·K -1 .

[0072] Example 3

[0073] This embodiment provides a method for preparing a high thermal conductivity cigarette core material, which is specifically as follows:

[0074] (1) 2 g of spherical alumina powder (20 μm) was dispersed in 300 mL of a mixed solution of isopropanol and deionized water (volume ratio 0.8:1), and the mixed solution was ultrasonically exfoliated at 25 °C for 24 h;

[0075] (2) centrifuging the mixed solution after stripping at 2000 rpm for 10 min, vacuum filtering the supernatant obtained after centrifugation, and drying to obtain hydroxylated nano-alumina particles;

[0076] (3) 1 g of hydroxylated nano-alumina particles was added to a mixed solution of 200 mL of ethanol and deionized water (volume ratio 4:1), and ultrasonically dispersed at 25°C for 1 h. Then, 1 mL of silane coupling agent KH570 was added to the mixed solution, and stirred in an oil bath at 100°C for 20 h under condensation reflux;

[0077] (4) After the solution is cooled to 25° C., the mixed solution is filtered, and the filtrate is dried at 100° C. for 12 h to obtain nano-alumina particles modified with a silane coupling agent;

[0078] (5) Weigh 1 g of guar gum and dissolve it in 99 g of deionized water to prepare a 1% guar gum aqueous solution, then add 1 g of the nano-alumina particles modified by the silane coupling agent, and stir ultrasonically at 25° C. for 18 h to obtain a thermal conductive slurry;

[0079] (6) using a pneumatic spray gun to evenly spray the thermal conductive slurry onto the surface of the tobacco sheet;

[0080] (7) Drying the impregnated tobacco sheet at 60° C. and 70% RH, with the dry weight of the thermal conductive slurry being the same as that in Example 1, and the drying time being 3 h;

[0081] (8) The tobacco slices were hot-pressed for 1 h using a flat plate vulcanizer at a pressure of 7 MPa and a temperature of 50° C. to obtain a high thermal conductivity tobacco core material.

[0082] The thermal conductivity of the cigarette core material obtained in this embodiment was measured by a thermal conductivity tester (TC 3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) and found to be 0.23 W·m -1 ·K -1 .

[0083] Example 4

[0084] This embodiment provides a method for preparing a high thermal conductivity cigarette core material, and the process is different from that of Example 1 only in that: in step (1), the "mixed solution of 300 mL of isopropanol and deionized water (volume ratio of 1:1)" is replaced by "a mixed solution of 300 mL of ethanol and deionized water (volume ratio of 1:1)", and other conditions remain unchanged.

[0085] The thermal conductivity of the cigarette core material obtained in this embodiment was measured by a thermal conductivity tester (TC 3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) and found to be 0.19 W·m -1 ·K -1 .

[0086] Example 5

[0087] This embodiment provides a method for preparing a high thermal conductivity cigarette core material, and the process is different from that of Example 1 only in that: in step (1), the "mixed solution of 300 mL of isopropanol and deionized water (volume ratio of 1:1)" is replaced by "a mixed solution of 300 mL of DMF and deionized water (volume ratio of 1:1)", and other conditions remain unchanged.

[0088] The thermal conductivity of the cigarette core material obtained in this embodiment was measured by a thermal conductivity tester (TC 3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) and found to be 0.18 W·m -1 ·K -1 .

[0089] Example 6

[0090] This embodiment provides a method for preparing a high thermal conductivity cigarette core material, and the process is different from that of Example 1 only in that: in step (1), "300 mL of a mixed solution of isopropanol and deionized water (volume ratio 1:1)" is replaced by "300 mL of deionized water", and other conditions remain unchanged.

[0091] The thermal conductivity of the cigarette core material obtained in this embodiment was measured by a thermal conductivity tester (TC 3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) and found to be 0.14 W·m -1 ·K -1 .

[0092] Example 7

[0093] This embodiment provides a method for preparing a high thermal conductivity cigarette core material, and the process is different from that of Example 1 only in that: in step (1), "a mixed solution of 300 mL of isopropanol and deionized water (volume ratio 1:1)" is replaced by "a mixed solution of 300 mL of isopropanol, ethanol and deionized water (volume ratio 0.8:0.2:1)", and other conditions remain unchanged.

[0094] The thermal conductivity of the cigarette core material obtained in this embodiment was measured by a thermal conductivity tester (TC 3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) and found to be 0.29 W·m -1 ·K -1 .

[0095] Example 8

[0096] This embodiment provides a method for preparing a high thermal conductivity cigarette core material, and the process is different from that of Example 1 only in that: in step (3), the "mixed solution of 200 mL of ethanol and deionized water (volume ratio of 3:1)" is replaced by "a mixed solution of 200 mL of isopropanol and deionized water (volume ratio of 3:1)", and other conditions remain unchanged.

[0097] The thermal conductivity of the cigarette core material obtained in this embodiment was measured by a thermal conductivity tester (TC 3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) and found to be 0.16 W·m -1 ·K -1 .

[0098] Example 9

[0099] This embodiment provides a method for preparing a high thermal conductivity cigarette core material, and the process is different from that of Example 1 only in that: in step (3), the "mixed solution of 200 mL of ethanol and deionized water (volume ratio of 3:1)" is replaced by "a mixed solution of 200 mL of isobutanol and deionized water (volume ratio of 3:1)", and other conditions remain unchanged.

[0100] The thermal conductivity of the cigarette core material obtained in this embodiment was measured by a thermal conductivity tester (TC 3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) and found to be 0.17 W·m -1 ·K -1 .

[0101] Example 10

[0102] This embodiment provides a method for preparing a high thermal conductivity cigarette core material, and the process is different from that of Example 1 only in that: in step (3), "a mixed solution of 200 mL of ethanol and deionized water (volume ratio 3:1)" is replaced by "200 mL of deionized water", and other conditions remain unchanged.

[0103] The thermal conductivity of the cigarette core material obtained in this embodiment was measured by a thermal conductivity tester (TC 3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) and found to be 0.12 W·m -1 ·K -1 .

[0104] Embodiment 11

[0105] This embodiment provides a method for preparing a high thermal conductivity cigarette core material, and the process is different from that of Example 1 only in that in step (3), "0.5 mL of silane coupling agent KH550" is replaced by "0.5 mL of silane coupling agent KH570", and other conditions remain unchanged.

[0106] The thermal conductivity of the cigarette core material obtained in this embodiment was measured by a thermal conductivity tester (TC 3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) and found to be 0.24 W·m -1 ·K -1 .

[0107] Example 12

[0108] This embodiment provides a method for preparing a high thermal conductivity cigarette core material, and the process is different from that of Example 1 only in that: in step (3), "0.5 mL of silane coupling agent KH550" is replaced by "0.3 mL of silane coupling agent KH550+0.2 mL of silane coupling agent KH570", and other conditions remain unchanged.

[0109] The thermal conductivity of the cigarette core material obtained in this embodiment was measured by a thermal conductivity tester (TC 3000E, Xi'an Xiaxi Electronic Technology Co., Ltd.) and found to be 0.28 W·m -1 ·K -1 .

[0110] The thermal conductivity coefficients of the high thermal conductivity cigarette core materials prepared in Examples 1-12 are summarized in the following table:

[0111] Group <![CDATA[Thermal conductivity (W·m -1 ·K -1 )]]> Before modification 0.10 Example 1 0.26 Example 2 0.25 Example 3 0.23 Example 4 0.19 Example 5 0.18 Example 6 0.14 Example 7 0.29 Example 8 0.16 Example 9 0.17 Example 10 0.12 Embodiment 11 0.24 Example 12 0.28

[0112] From the data results in the above table, it can be seen that the thermal conductivity of the cigarette core material can be significantly improved by modifying the cigarette core material by the method involved in the present invention, that is, the thermal conductivity of the cigarette core material is significantly improved. In addition, the reaction medium selected in the hydroxylation process and the silane coupling agent modification process will affect the thermal conductivity of the product, and the type of silane coupling agent selected will also have a certain impact on the thermal conductivity of the product.

[0113] The applicant declares that the present invention illustrates the technical solution of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0114] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0115] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. A method for preparing a high thermal conductivity cigarette core material, characterized in that: The preparation method comprises the following steps: (1) dispersing a thermally conductive filler powder in a stripping solvent for stripping and hydroxylation to obtain hydroxylated thermally conductive filler nanoparticles; (2) dispersing the hydroxylated thermally conductive filler nanoparticles in a solution containing a silane coupling agent and performing a heat treatment to obtain thermally conductive filler nanoparticles modified with a silane coupling agent; (3) mixing the thermally conductive filler nanoparticles modified by the silane coupling agent with the adhesive aqueous solution for dispersion treatment to obtain a thermally conductive slurry; (4) Distributing the thermal conductive slurry on the surface of the cigarette core material, drying it, and then heat-pressing it to obtain the high thermal conductive cigarette core material.

2. The method for preparing a high thermal conductivity cigarette core material according to claim 1, characterized in that: The thermally conductive filler in step (1) is selected from any one or a combination of at least two of boron nitride, aluminum nitride, graphene oxide, carbon nanotubes, silicon carbide, magnesium oxide, aluminum oxide, zinc oxide, silicon dioxide or thermally conductive metal powder; Preferably, the mass ratio of the thermally conductive filler powder to the stripping solvent in step (1) is (0.1-5):

100.

3. The method for preparing a high thermal conductivity cigarette core material according to claim 1 or 2, characterized in that: The stripping solvent in step (1) is a mixed solution of water and any one or at least two of the following organic solvents: isopropanol, isobutanol, ethanol, polyvinyl alcohol, DMF; Preferably, the volume ratio of water to organic solvent is 1:(0.8-1.2); Preferably, the stripping solvent is a mixed solution of water, isopropanol and ethanol; Preferably, the volume ratio of isopropanol to ethanol is (3-5):

1.

4. The method for preparing a high thermal conductivity cigarette core material according to any one of claims 1 to 3, characterized in that: The stripping and hydroxylation treatment in step (1) is carried out under ultrasound, the ultrasound temperature is 15-40° C., and the ultrasound time is 10-24 h.

5. The method for preparing a high thermal conductivity cigarette core material according to any one of claims 1 to 4, characterized in that: The solution in step (2) is a mixed solution of water and any one or at least two of the following organic solvents: isopropanol, isobutanol, ethanol, polyvinyl alcohol, DMF; Preferably, the volume ratio of water to organic solvent is 1:(2-4); Preferably, the solution is a mixed solution of water and ethanol.

6. The method for preparing a high thermal conductivity cigarette core material according to any one of claims 1 to 5, characterized in that: In the solution containing the silane coupling agent in step (2), the mass percentage of the silane coupling agent is 0.1-1%; Preferably, the silane coupling agent in step (2) is selected from any one of KH550, KH560, KH570, A151, A171 or Si-69, or a combination of at least two thereof; Preferably, the silane coupling agent in step (2) is selected from KH550 and / or KH570; Preferably, the mass ratio of the hydroxylated thermally conductive filler nanoparticles to the solution containing the silane coupling agent in step (2) is (0.1-5):100; Preferably, the heating treatment in step (2) is carried out by stirring, condensing and reflux in a 90-100° C. oil bath for 18-30 hours.

7. The method for preparing a high thermal conductivity cigarette core material according to any one of claims 1 to 6, characterized in that: The adhesive in step (3) is selected from any one of sodium alginate, sodium carboxymethyl cellulose, chitosan, guar gum or cellulose acetate, or a combination of at least two thereof; Preferably, the mass ratio of the thermally conductive filler nanoparticles modified by the silane coupling agent to the adhesive in step (3) is (1-5):1; Preferably, the concentration of the adhesive aqueous solution in step (3) is 0.25-1%; Preferably, the dispersion treatment in step (3) is carried out under ultrasound, the ultrasound temperature is 15-40° C., and the ultrasound time is 8-24 h.

8. The method for preparing a high thermal conductivity cigarette core material according to any one of claims 1 to 7, characterized in that: The cigarette core material in step (4) is in the form of a thin sheet; Preferably, the distribution method in step (4) includes dipping or spraying; The dipping method is to immerse the cigarette core material into the thermal conductive slurry for 2-30 seconds and then take it out; the spraying method is to spray the thermal conductive slurry evenly on the surface of the cigarette core material; Preferably, the drying treatment in step (4) is carried out at 40-60° C. and a humidity of 50-70% RH; Preferably, the dry weight of the thermal conductive slurry in step (4) is loaded on the surface of the cigarette core material in an amount of 0.1-1 mg / cm 2 ; Preferably, the hot pressing treatment in step (4) is carried out at 30-50°C and a pressure of 5-14 MPa.

9. A high thermal conductivity cigarette core material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the high thermal conductivity cigarette core material according to claim 9 in preparing heated cigarettes.